Field notes contributed by Randall Pinkston, summer 1993 - Pinkston, Randallet al (1993)
Summer report of birds and locations contributed by Randall Pinkston. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1993. Plustek - flatbed